2012
DOI: 10.1021/jf303271p
|View full text |Cite
|
Sign up to set email alerts
|

Low Sorption and Fast Dissipation of the Herbicide Saflufenacil in Surface Soils and Subsoils of an Eroded Prairie Landscape

Abstract: Saflufenacil partitioning and dissipation were evaluated in soils from an eroded prairie landscape to provide information on its expected environmental fate. Saflufenacil K(d) values followed trends in soil organic carbon content. In surface soils, K(d) values ranged from 0.05 to 0.2 L kg(-1) in the depositional lower slope and from 0.02 to 0.06 L kg(-1) in the eroded upper slope. In subsurface soils, K(d) values were an order of magnitude higher in the lower slope (mean 0.1 L kg(-1)) than in the upper slope (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…Low sorption of this herbicide in soils with clayey and medium texture has been observed. A positive correlation has been observed between the saflufenacil sorption and the increase in organic carbon content in the soil (PAPIERNIK et al, 2012;MATALLO et al, 2014).…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Low sorption of this herbicide in soils with clayey and medium texture has been observed. A positive correlation has been observed between the saflufenacil sorption and the increase in organic carbon content in the soil (PAPIERNIK et al, 2012;MATALLO et al, 2014).…”
Section: Introductionmentioning
confidence: 82%
“…g dm Papiernik et al (2012); Matallo et al (2014) reported that saflufenacil has a low sorption coefficient in medium textured soils, thus, it may be available in the root zone for uptake by plants. Therefore, a sandy soil was used in this study to ensure that the herbicide became available in the root zone for uptake by the plants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Papiernik et al (2012), the half-life of saflufenacil ranges from 13 (in the arable layer) to 32 days (in the subsurface layer), with low soil sorption and rapid dissipation. However, injuries were observed in rotational crops (pumpkin, cucumber, carrots, garlic, pepper and beet) up to one year after high herbicide doses (100 to 200 g a.i.…”
Section: Effects Of the Herbicides Saflufenacil And Indaziflam On Agrmentioning
confidence: 99%
“…18 As a result, this highly effective herbicide was likely to have been nearly ignored in Bridges' calculations. Moreover, the yield loss estimates from Bridges that are used throughout the ABT economic calculations are based entirely on a one-for-one substitution of a single alternative herbicide treatment for atrazine.…”
Section: Alternative Herbicidesmentioning
confidence: 99%